“ONE NATION ONE ELECTION”: A COMPREHENSIVE ANALYSIS - Deo, Mangal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
One of the main characteristics of a democratic system is the periodic holding of elections. Every five years, India conducts regular, fair elections at the national, state, and local levels, which form the foundation of its democratic system. The notion of "One Nation, One Election" (ONOE) has prompted heated discussion among India's political and intellectual elite. It noted that the election campaigns cost a lot of money and take up almost a year. The NDA government has proposed a "One Nation-One Election" plan to reduce the time and energy spent on conducting several state elections. The initiative seeks to coordinate the timing of elections for India's federal parliament and regional legislative bodies, minimizing the number of separate electoral events. Proponents say that ONOE would result in significant cost savings, decrease administrative burdens, and improve governance stability. Critics, on the other hand, highlight to the constitutional, legal, and logistical problems, as well as the possible negative repercussions on the country's federal system. The objective of this paper is to present a thorough examination of the ONOE idea, including its historical background, pro and con arguments, and consequences for the Indian democracy.